2011
DOI: 10.1111/j.1365-2354.2009.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patients' needs and doctors' perceptions of information requirements related to a diagnosis of oesophageal or gastric cancer

Abstract: The aim of this study was to assess the information needs of patients diagnosed with oesophageal and gastric cancer and to compare these with their perceived information needs in the opinion of junior doctors. One hundred patients and 100 doctors responded to a questionnaire regarding the information needs of cancer patients. Seventy-nine per cent of patients wanted as much information as possible about their diagnosis, but only 35% of doctors were willing to give all the available information (P < 0.0001). Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 23 publications
(39 reference statements)
1
35
1
3
Order By: Relevance
“…From a clinical perspective it is often argued that honest information can lead to a lack of belief in recovery and also that withholding honest information can be a way of protecting the patients. These arguments are not in line with the results of this study where it is clear that the patients' experience that the HCPs underestimate their information needs; a fact that has also been shown in earlier studies (Andreassen et al, 2007;Wittmann et al, 2011). It is known that the patients wish to be given information about what to expect after surgery in relation to remaining symptoms and prognosis (Malmström et al, 2013;Sainio and Eriksson, 2003) but Stajduhar et al (2010) states that it is important to balance hope and honesty in the provision of information to patients with cancer.…”
Section: Results Considerationscontrasting
confidence: 59%
“…From a clinical perspective it is often argued that honest information can lead to a lack of belief in recovery and also that withholding honest information can be a way of protecting the patients. These arguments are not in line with the results of this study where it is clear that the patients' experience that the HCPs underestimate their information needs; a fact that has also been shown in earlier studies (Andreassen et al, 2007;Wittmann et al, 2011). It is known that the patients wish to be given information about what to expect after surgery in relation to remaining symptoms and prognosis (Malmström et al, 2013;Sainio and Eriksson, 2003) but Stajduhar et al (2010) states that it is important to balance hope and honesty in the provision of information to patients with cancer.…”
Section: Results Considerationscontrasting
confidence: 59%
“…Recent studies have shown that, despite increasing awareness and knowledge among clinicians about the information needs of cancer patients, many patients still feel that they do not get enough information or have received information that is unclear and not understandable [12,14,15].…”
Section: Introductionmentioning
confidence: 97%
“…In addition, a patient's desire to understand a suspected genetic condition as a way of coping [52] may run counter to the techniques medical professionals use to dispense information. A study by Wittmann et al [58] found that 79 % of patients wanted as much information as possible about their diagnosis, whereas only 35 % of physicians were willing to provide all of the information at their disposal.…”
Section: Influence Of the Internet As A Common Source Of Informationmentioning
confidence: 99%